2017
DOI: 10.1139/facets-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of run sprint interval training on healthy, inactive, overweight/obese women: A pilot study

Abstract: This study examined the effects of a 12 week, treadmill-based, run sprint interval training (SIT) protocol compared with that of a moderate-intensity continuous training (MICT) protocol in healthy, inactive, overweight/obese women, on cardiovascular disease risk factors. After random assignment, the SIT group completed 4-10 × 30 s maximal sprints, with a 4 min active recovery between sprints, and the MICT group completed 30-60 min at moderate intensity (45-55% heart rate reserve (HRR)). The rate of perceived e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Allison and colleagues [ 52 ] found that a low-volume SIT protocol, involving 3 × 20 s stair climbing-based sprints, increased V̇O 2 peak in inactive young women to a comparable extent as that previously observed with 3 × 20 s cycling sprints (~ 12%; [ 53 ]) when performed thrice-weekly for 6 weeks. Improved CRF was also observed following 6–12 weeks of running-based SIT, involving 4–10 × 30 s sprints, in recreationally active women [ 54 ] and inactive women with overweight/obesity [ 55 ], and walking-based HIIT, involving 6 × 1 min efforts at 90% heart rate reserve, in older women (60–85 years) with T2D [ 56 ]. However, V̇O 2 peak has been reported to be unchanged following 8–16 weeks of thrice-weekly 6–10 × 1 min low-volume HIIT that used running/walking intervals in women who are older (60–75 years) [ 57 ] or with polycystic ovary syndrome [ 58 ].…”
Section: Cardiorespiratory Fitnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Allison and colleagues [ 52 ] found that a low-volume SIT protocol, involving 3 × 20 s stair climbing-based sprints, increased V̇O 2 peak in inactive young women to a comparable extent as that previously observed with 3 × 20 s cycling sprints (~ 12%; [ 53 ]) when performed thrice-weekly for 6 weeks. Improved CRF was also observed following 6–12 weeks of running-based SIT, involving 4–10 × 30 s sprints, in recreationally active women [ 54 ] and inactive women with overweight/obesity [ 55 ], and walking-based HIIT, involving 6 × 1 min efforts at 90% heart rate reserve, in older women (60–85 years) with T2D [ 56 ]. However, V̇O 2 peak has been reported to be unchanged following 8–16 weeks of thrice-weekly 6–10 × 1 min low-volume HIIT that used running/walking intervals in women who are older (60–75 years) [ 57 ] or with polycystic ovary syndrome [ 58 ].…”
Section: Cardiorespiratory Fitnessmentioning
confidence: 99%
“… Studies were conducted in women who were classified as healthy [ 10 , 46 , 47 , 49 , 52 , 54 , 65 , 69 72 , 75 , 79 , 161 ], with overweight/obesity [ 44 , 50 , 51 , 53 , 55 , 60 63 , 66 , 67 , 73 , 76 , 100 , 110 , 121 , 138 , 162 , 164 , 167 , 168 ] and/or type 2 diabetes [ 100 , 162 ]. For transparency, the same cohort of women was examined in the following pairs of references: [ 50 , 121 ] and [ 73 , 138 ].…”
Section: Cardiorespiratory Fitnessmentioning
confidence: 99%
“…A total of 2,542 studies were identified from the database after initial search. After de-duplication and title and abstract screening, 60 studies were retrieved and screened by full-text, and 25 studies were included in the current review ( Tritter et al, 2013 ; Sim et al, 2014 ; Foster et al, 2015 ; Stork et al, 2015 , 2018 , 2019 ; Kong et al, 2016 ; Wood et al, 2016 ; Rowley et al, 2017 ; Townsend et al, 2017 ; Follador et al, 2018 ; Kriel et al, 2018 , 2019 ; McKie et al, 2018 ; Niven et al, 2018 ; Olney et al, 2018 ; Astorino et al, 2019 , 2020 ; Bradley et al, 2019 ; Marin et al, 2019 ; Wilke et al, 2019 ; Marques et al, 2020 ; Metcalfe et al, 2020 ; Schaun and Alberton, 2020 ; Songsorn et al, 2020 ; Hu et al, 2021 ). A flow chart presented the Figure 1 demonstrated the completed steps of selections of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Close to half of the studies (i.e., 11 out of 25 studies) involved active participants with high cardiorespiratory fitness level indicated by above average VO 2max ranging from 40–55 ml kg –1 min –1 . Three studies analyzed affective responses from overweight females ( Rowley et al, 2017 ; Astorino et al, 2019 ) and males ( Sim et al, 2014 ) and one study from women with excess weight ( Hu et al, 2021 ), whereas all the other studies focused on normal weight participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation